How four year olds spend their day: Insights into the Caring contexts of young Children - Baxter, Jennifer; Hayes, A (My University, 2007)
The ways children spend their time both reflect and contribute to developmental changes and developmental differences. This article analyses the time use data of 4-5 year olds from Growing Up in Australia: the Longitudinal Study of Australian Children study, to describe the children's overall activity patterns, and to examine whether time use is affected by social, physical, and emotional development outcomes, parent education and employment, or family size and form. Time use data is presented for time spent on personal care and eating, television watching, exercise, achievement-oriented play, social and organised activities, travel, sleeping and resting. The findings show that children spend much of their time in playing, personal care, and social and organised activities. Age, gender, family size, maternal employment, and parental education affected time use. The analyses in this paper are based on a single wave of data and as the longitudinal study progesses it will be possible to explore the relationships more fully and to examine questions, such as, whether parenting style mediates some of these relationships and to what extent, the impact of parental presence or absence, and to location - home versus outside home.
Keywords: Activities -- Children's Activities; Activities; Childhood and child development; Activities; Children's Activities; Childhood and child development